Gaseous secondary injection thrust vector control device - DUNAWAY; J. C; JACOBS; PAUL L (1987)
Apparatus for modulating the thrust vector of a rocket motor by injecting hot gas into the divergent section of the rocket nozzle and modulating injection of the hot gas by varying the flow from a solid propellant gas generator by controlling its flow rate with a vortex throttling valve arrangement.